Improvement of mechanical properties of β-stabilized intermetallics of TiAl system by zone recrystallization method - Lobanov, L.M.; Asnis, E.A.; Piskun, N.V.; Statkevich, I.I. (Reports of the National Academy of Sciences of Ukraine, 2020)
We investigate the mechanical properties of the intermetallic alloy of the TiAl system of the composition Ti-44Al- 5Nb-3Cr-1.5Zr (at.%), which was remelted in order to optimize the structure and properties by the method of induction float zone melting (FZ-processing). The method of tensile and compressive tests of the intermetallide of the TiAl system, both in the initial state and after the crucibleless induction zone melting, has been developed. The results of tensile tests of the source material showed that the tensile strength at room temperature (+ 20 °C) is 240.5 MPa, and ductility is practically not observed. An analogous test of samples, which passed the test using the IBZP method, showed a yield limit of 837 MPa, ultimate strength of 983 MPa, and tensile elongation δ — 1.45%. Intermetallics of the TiAl system at room temperature are low-plasticity materials, and the brittle fracture of the sample when tested for uniaxial tension occurs immediately in the elastic region. Due to the fact that the compression is one of the mildest types of tests, it was decided to perform further tests to determine the mechanical characteristics of compression. The studies were performed on a machine Instron 8802 using special devices designed for flat and cylindrical specimens in accordance with the standard ASTM D695. This allowed us to determine such mechanical characteristics as the yield limit and ultimate strength, as well as the degree of deformation under the compression ε %, for the source material. Deformation curves were constructed from these data. In order to compare the mechanical properties of the initial alloy, which were obtained by different test methods — tensile and compressive, we also tested the samples for the compression after the zone recrystallization. It is shown that the mechanical properties of the alloy, which were determined in the compression test, are much higher than those obtained in the tensile test.